Evaluasi pemanfaatan dana desa di Desa Rumoong Atas Kecamatan Tareran Kabupaten Minahasa Selatan - Karundeng, Thriver Merelygod; Runtu, Treesje; Lintong, Diana N. (Yayasan Widyantara Nawasena Raharja, 2025)
This study evaluates the utilization of Village Funds in Rumoong Atas Village, Tareran District, South Minahasa Regency, Indonesia, in accordance with the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration (Permendes PDTT) No. 13 of 2023. The regulation prioritizes the allocation of Village Funds for four main programs: extreme poverty alleviation, food and livestock security, stunting prevention and reduction, and priority sector development. Using a qualitative descriptive method, data were collected through documentation, interviews, and direct observation of the village government’s implementation of these programs. The findings show that the implementation of Village Fund programs in Rumoong Atas Village partially complies with the regulation. The village did not implement the direct cash transfer (BLT) program for extreme poverty alleviation but successfully carried out programs on food and livestock security, stunting prevention, and priority sector development, including additional capital for village-owned enterprises (BUMDes). This study contributes to the evaluation of local government performance in managing Village Funds and highlights areas for policy improvement to enhance community welfare and accountability.